2013
DOI: 10.4236/ojms.2013.32a005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Photoperiod, Temperature and Feeding Regimes on the Respiration Rates of Antarctic Krill (<i>Euphausia superba</i>)

Abstract: Antarctic krill is thought to undergo an annual cycle of biological processes to cope with seasonal changes in their environment. The question of whether, and to what degree, seasonal environmental parameters such as photoperiod, food availability and temperature govern metabolism in krill is not clear. In this long-term laboratory study, respiration rates were determined in krill incubated under simulated natural light cycle or total darkness, subjected to fed or starved conditions and on krill kept at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…The presence of food alone is not sufficient to trigger feeding activity (Atkinson et al 2002;Teschke et al 2007). Recent research indicated that endogenous (inherent) mechanisms exist to synchronise the seasonal and circadian rhythmicity of metabolic and physiological output (Teschke et al 2007(Teschke et al , 2008(Teschke et al , 2011Mazzotta et al 2010), triggered by light (Seear et al 2009;Teschke et al 2011;Brown et al 2013). On the other hand, it was clearly shown in short-term starvation experiments that food availability does play a role: even after only 18 days without food, krill switched to a mode that reduced energy consumption and initiated consumption of body lipids (Atkinson et al 2002;Auerswald et al 2009).…”
Section: Original Papermentioning
confidence: 99%
“…The presence of food alone is not sufficient to trigger feeding activity (Atkinson et al 2002;Teschke et al 2007). Recent research indicated that endogenous (inherent) mechanisms exist to synchronise the seasonal and circadian rhythmicity of metabolic and physiological output (Teschke et al 2007(Teschke et al , 2008(Teschke et al , 2011Mazzotta et al 2010), triggered by light (Seear et al 2009;Teschke et al 2011;Brown et al 2013). On the other hand, it was clearly shown in short-term starvation experiments that food availability does play a role: even after only 18 days without food, krill switched to a mode that reduced energy consumption and initiated consumption of body lipids (Atkinson et al 2002;Auerswald et al 2009).…”
Section: Original Papermentioning
confidence: 99%
“…from regions across the whole Antarctic Ocean. This pattern shows evidence for a general metabolic strategy in E. superba, which has been investigated from the molecular (Seear et al, 2009;Teschke et al, 2011) to the organism level Teschke et al, 2007;Gaten et al, 2008;Pape et al, 2008;Brown et al, 2013). Although, the signaling cascade that links the photoperiod cue to the target response still remains unknown, the photoperiodic cycle clearly seems to act as a major Zeitgeber for the seasonal cycle of RR, suggesting that krill has evolved an endogenous time keeping system that perceives seasonal variations in photoperiod (Meyer, 2011).…”
Section: Seasonal Respiration Models For Single Euphausiid Speciesmentioning
confidence: 91%
“…Thus, the seasonal cycle of RR in krill could be linked to an endogenous timing system, synchronized with the seasonal course of photoperiod in the environment. In a long-term experimental study lasting several years, Brown et al (2013) maintained E. superba first under simulated natural photoperiod, before they exposed part of the group to complete darkness and variable food availability and temperature over several months. These experiments showed that E. superba maintained similar RR patterns under constant darkness as under a simulated natural light regime.…”
Section: Seasonal Respiration Models For Single Euphausiid Speciesmentioning
confidence: 99%
“…Current experimental procedures typically necessitate krill being sacrificed to determine any effect of environmental change on krill anatomy (e.g. Brown et al, 2013).…”
Section: Optical Coherence Tomography (Oct) Is a Non--invasive High-mentioning
confidence: 99%
“…Observing any environmentally induced physiological effect typically requires the sacrifice of individual animals precluding repeated measures type analysis and requiring large control and treatment group sizes (e.g. Brown et al, 2013).…”
Section: Introductionmentioning
confidence: 99%